The perception of accountants on IFRS adoption: Evidence from Libya - Albaskri, Ibrahim K.M. (2015)
International Financial Reporting Standards (IFRS) is being adopted by many countries in the world. The purpose of this study is to examine factors that affect an adoption of IFRS in Libya from the perception of Libyan companies’ accountants. This study has been conducted using a survey of 288 distributed questionnaires in 2015. The questionnaires have been distributed to Libyan companies’ accountants. The results reveal that professional bodies and government policy positively significant to an adoption of IFRS in Libya. However, capital market and education level are not significant to the adoption of IFRS in Libya